2018
DOI: 10.1016/j.vaa.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral α2-adrenoceptor antagonism affects the absorption of intramuscularly coadministered drugs

Abstract: MK-467 accelerated the absorption of IM coadministered drugs. This is clinically relevant as it may hasten the onset of peak sedative effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Although this result may be influenced by the limitation observed in the IM group, where the first sampling times were taken at variable times, that may have hindered the evaluation of a real absorption in the first 30 min after administration, the presence of higher drugs concentrations and AUCs after IM route agrees with the studies reported byPorters et al (2014) andWells et al (2008). Moreover, the IM route showed a tendency of a longer T max (p > 0.05) for MET than DEX (30 vs. 20 min, respectively), resulting in an agreement with data reported byKallio-Kujala et al (2018).Clearly, the induction and maintenance of general anaesthesia may have influenced the kinetic profile of DEX and MET for both routes of administration. In fact, the variability in the drugs serum concentrations was particularly observed during the anaesthetic period(Figures 1 and 2), to support a probable effect on the two molecules' redistribution, anyway difficult to explain in this clinical pharmacokinetic study.…”
supporting
confidence: 90%
See 4 more Smart Citations
“…Although this result may be influenced by the limitation observed in the IM group, where the first sampling times were taken at variable times, that may have hindered the evaluation of a real absorption in the first 30 min after administration, the presence of higher drugs concentrations and AUCs after IM route agrees with the studies reported byPorters et al (2014) andWells et al (2008). Moreover, the IM route showed a tendency of a longer T max (p > 0.05) for MET than DEX (30 vs. 20 min, respectively), resulting in an agreement with data reported byKallio-Kujala et al (2018).Clearly, the induction and maintenance of general anaesthesia may have influenced the kinetic profile of DEX and MET for both routes of administration. In fact, the variability in the drugs serum concentrations was particularly observed during the anaesthetic period(Figures 1 and 2), to support a probable effect on the two molecules' redistribution, anyway difficult to explain in this clinical pharmacokinetic study.…”
supporting
confidence: 90%
“…These results were explained with the same hypotheses, (high administration volume, ptyalism and peripheral vasoconstriction). Additionally, DEX‐induced peripheral vasoconstriction was also observed by other authors in IM route of administration (Kallio‐Kujala et al, ; Pypendop, Honkavaara, & Elkiw, ).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations